New methods in vocabulary teaching in the CSL Classroom / Hui Yin - Yin, Hui (Universiti Teknologi MARA, Kedah, 2014)
Teaching vocabulary in the CSL (Chinese as Second Language) classroom is a challenge that many teachers face and traditional grammar-translation methods seem not to be very effective in CSL vocabulary teaching. This study seeks to explore new methods which are different from grammar-translation methods in vocabulary teaching in the CSL classroom in order to change the situation from passive learning into active learning and from teacher-centered classes into student-centered ones. Various new methods such as synonym/antonym seeking, teaching through other semantic relations, teaching through analogy, teaching through brainstorming and associations, teaching through elicitation, and teaching through analyzing compounds are introduced in this study to provide students opportunities to learn language through using language and to make CSL vocabulary teaching more effective.